To solve the system of equations, we can use the substitution method.
First, we solve the first equation for x in terms of y:
-8x - 9y = -30
-8x = 9y - 30
x = (9y - 30)/-8
Substituting this expression for x into the second equation:
-2(9y - 30)/8 - 2y = -8
-18y + 60/8 - 2y = -8
-18y - 16y + 60 = -8
-34y + 60 = -8
-34y = -68
y = -68/-34
y = 2
Now that we have the value of y, we can substitute it back into the first equation to find x:
-8x - 9(2) = -30
-8x - 18 = -30
-8x = -12
x = -12/-8
x = 3/2
So the solution to the system of equations is x = 3/2 and y = 2.
−8x−9y=−30 and minus, 2, x, minus, 2, y, equals, minus, 8−2x−2y=−8.
1 answer